Allele mining in diverse accessions of tropical grasses to improve forage quality and reduce environmental impact - Hanley, Steve J; Pellny, Till K.; Vega, Jose J. de; Castiblanco, Valheria; Arango, Jacobo; Eastmond, Peter J.; Heslop-Harrison, J.S.; Mitchell, Rowan A. C. (Oxford University Press, 2021)
The C4Urochloa species (syn. Brachiaria) and Megathyrsus maximus (syn. Panicum maximum) are used as pasture for cattle across vast areas in tropical agriculture systems in Africa and South America. A key target for variety improvement is forage quality: enhanced digestibility could decrease the amount of land required per unit production, and enhanced lipid content could decrease methane emissions from cattle. For these traits, loss-of-function (LOF) alleles in known gene targets are predicted to improve them, making a reverse genetics approach of allele mining feasible. We therefore set out to look for such alleles in diverse accessions of Urochloa species and Megathyrsus maximus from the genebank collection held at the CIAT.